Faktor-Faktor Yang Mempengaruhi Niat Penggunaan Approweb Oleh Account Representative Direktorat Jenderal Pajak - Wakhid Nanang Santoso; Doddy Setiawan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to investigate the effect of performance expectancy, effort expectancy, social influence, web self efficacy, perceived security controls, and perceived enjoyment on the intention to use the approweb by account representative at the Directorate General of Taxation.The study employ web survey to collect data from account representative throughout Indonesia. There are 417 questionaire return from web survey.The results show that the performance expectancy, effort expectancy, social influence, perceived security control, and perceived enjoyment positively effect on the intention to use approweb, whereas the web self efficacy has no effect on the intentions to use approweb by account representative at the Directorate General of Taxation. The higher performance expectancy, effort expectancy, social influence, perceived security control, and perceived enjoyment will increase intention to use Approweb.